Factors Affecting Company Value of Consumer Goods Sector at Indonesia Stock Exchange - Mujiyono; Nany, Magdalena (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Company value reflects the level of success of a company's management.The aim of this research is to obtain empirical evidence about the influence of profitability, solvency, company size, independent audit committee and independent commissioners on company value partially.The population in this research is all consumer goods sector companies listed on the IDXperiod 2018 – 2020.The data in this research will be analyzed using multiple regression analysis.Partially, profitability, company size, independent audit committees and independent commissioners have significant positive effect on the value of the company. While solvency has a significant negative effect on the value of the company.